THEORETICAL STUDIES OF THE HEATING SYSTEM IN THE VEHICLE COMPARTMENT DURING PASSENGER TRANSPORTATION TAKING INTO ACCOUNT BREATHING UNDER CONDITIONS OF LOW TEMPERATURES - Aleshkov, Denis; Banket, Mikhail; Sukovin, Mikhail; Pogulyaeva, Irina; Yanchij, Svetlana (Journal of Applied Engineering Science, 2020)
This paper presents the results of theoretical computer-aided research of the microclimate parameters in the vehicle passenger compartment during operation of one of the widely used schemes of heating system in the passenger compartment, taking into account the breathing of passengers. Theoretical researches of the heating system operation in the passenger compartment taking into account passenger breathing have been conducted. Distribution of microclimate parameters in the passenger compartment cross-section, in the case of using a heating system having one compartment heater, with and without taking into account the breathing of passengers, has been obtained. The assessment of the effect of passengers' breathing on the microclimate parameters in the passenger compartment has been carried out. The outcomes of this research may be of interest to specialists involved in the design and ergonomics of wheeled vehicles and labor protection.
Keywords: heating system, microclimate parameters, thermal comfort